A pilot study exploring the relationship between wellness and physical fitness: an examination into autonomic health. Issue 7 (2nd October 2020) - Oliver, Michael D.; Morton, Alvin L.; Baldwin, Debora R.; Datta, Subimal
Abstract: Objective: To explore the relationship between physical fitness and wellness in order to determine if perceptions of wellness can be predicted by physical fitness level. Participants: Sixty-seven college students (41 females; M  = 20.86 years, SD = 4.23 years) were recruited from a large southeastern university during March–May 2018. Methods: Baseline measures for skin conductance and heart rate variability were obtained. Participants completed a wellness questionnaire and a series of tests (body composition, cardiorespiratory fitness, flexibility, and muscular fitness) designed to determine physical fitness levels. Correlation and regression analyses were run to explore relationships between physical fitness and wellness measures. Results: Muscular fitness and composite physical fitness significantly predicted perceived wellness. Heart rate variability was significantly related to physical fitness components. Conclusion: College students endorse muscular fitness as representative of health status; suggesting that by remaining physically active, in particular through muscular fitness, college student quality of life and cardiovascular health can be improved.